2018
DOI: 10.3889/oamjms.2018.054
|View full text |Cite
|
Sign up to set email alerts
|

Vitiligo in Children: A Review of Conventional Treatments

Abstract: Vitiligo is an important skin disease of childhood, which may lead to deep psychological trauma, resulting in a poor quality of life and low self-esteem. The Authors discuss a short review of the more conventional therapies available for the treatment of vitiligo in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 24 publications
0
11
0
1
Order By: Relevance
“…Topical corticosteroids are are considered the first line treatment for limited vitiligo, <20% of body surface area 6 , explaining its use by 92% (n=111) of patients in this study. Several studies have shown that topical corticosteroids is moderately effective to induce repigmentation of vitiligo+24.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Topical corticosteroids are are considered the first line treatment for limited vitiligo, <20% of body surface area 6 , explaining its use by 92% (n=111) of patients in this study. Several studies have shown that topical corticosteroids is moderately effective to induce repigmentation of vitiligo+24.…”
Section: Discussionmentioning
confidence: 90%
“…Despite vitiligo was reported to affects both genders in equal proportions in adults and sometimes in children 7 , childhood vitiligo tends to affect females more frequently than males. 6 A study by El-Husseiny R et al 2020 8 involving 483 child with vitiligo observed that females were affected in 59.1% (n=130) of patients. In addition, similar results were observed by Shajil et al 2006 9 and Nunes & Esser 2011 10 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Topical vitamin D analogues are thought to have an impact by making an immunomodulation and melanogenesis stimulation through vitamin D receptors (34)(35)(36)(37). A study on the subject has reported success in 10 cases out of 18 children (31).…”
Section: Discussionmentioning
confidence: 99%
“…The repigmentation in vitiligo is believed to be linked to a synergistic effect of all the antioxidant action of these herbal bio-actives. The availability of any new treatment that can reduce the use of UVB from high to low, and still be efficacious, is of immense benefit to both patients and treating physicians [21], [22], [23], [24], [25], [26], [27], [28], [29].…”
Section: Discussionmentioning
confidence: 99%